Sensing Technologies used for Monitoring and Detecting Insect Infestation in Stored Grain - Kaushik, Rekha; Singhai, Jyoti (International Journal of Engineering and Technology, 2018)
In India, the production of grain has been steadily increasing. Improper storage of grain results in higher losses in terms of quality as well as quantity. Contamination of grain occurs due to insects and micro-organisms present in it. Their presence and growth highly depends on environmental factors. When grain gets infested, volatile compounds get accumulated and release odour. The rapid growth of sensing technology makes the early and accurate detection of insects/fungi more promising. This paper discusses about different kinds of sensing technologies such as environmental sensing, acoustic sensing, odour sensing and image sensing, their working, challenges and issues, advantages and limitations. Future trends of using sensing technology are also discussed.Â Â